2019
DOI: 10.1093/joc/jqz014
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Narrative Correctives to Combat Misinformation†

Abstract: Misinformation can influence personal and societal decisions in detrimental ways. Not only is misinformation challenging to correct, but even when individuals accept corrective information, misinformation can continue to influence attitudes: a phenomenon known as belief echoes, affective perseverance, or the continued influence effect. Two controlled experiments tested the efficacy of narrative-based correctives to reduce this affective residual in the context of misinformation about organic tobacco. Study 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 66 publications
(84 reference statements)
0
46
1
1
Order By: Relevance
“…Among these is the journalistic practice that reduces abstract topics, such as vaccination refusal or hesitancy, to personal stories. News accounts about a parent who fears or reports a child’s experience with a side effect cannot be simply debunked as inaccurate or treated as misinformation in and of itself [ 5 ]. The U.S. Centers for Disease Control reports that the possible risks of the MMR vaccine include (a) soreness, redness, or rash, (b) fever or swelling of the glands in the cheeks or neck, or (c) in more serious cases, seizures, pneumonia, swelling of brain, and unusual bleeding [ 6 ].…”
Section: The Effects Of Scientific Messages and Narratives About Vaccinationmentioning
confidence: 99%
“…Among these is the journalistic practice that reduces abstract topics, such as vaccination refusal or hesitancy, to personal stories. News accounts about a parent who fears or reports a child’s experience with a side effect cannot be simply debunked as inaccurate or treated as misinformation in and of itself [ 5 ]. The U.S. Centers for Disease Control reports that the possible risks of the MMR vaccine include (a) soreness, redness, or rash, (b) fever or swelling of the glands in the cheeks or neck, or (c) in more serious cases, seizures, pneumonia, swelling of brain, and unusual bleeding [ 6 ].…”
Section: The Effects Of Scientific Messages and Narratives About Vaccinationmentioning
confidence: 99%
“…To the best of our knowledge, only one study has investigated the effectiveness of narrative corrections. Sangalang et al ( 2019 ) explored whether narrative corrections could reduce smokers’ misinformed beliefs about tobacco. Results were inconclusive, as a narrative correction was found to reduce misconceptions in only one of the two experiments reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies looked at very specific types of emotional flow and did not examine the manipulation of flow systematically. At the same time, other studies, including our own set of experiments (Sangalang, Ophir, & Cappella, 2019) failed to provide empirical support for the notion that emotional flow enhances engagement and persuasion. In fact, some studies found short EE stories consisting of only one consistent emotion to be more engaging and persuasive than those consisting of emotional shifts (McAllister, 2020).…”
Section: Why Emotional Shifts Are Expected To Increase Engagement Andmentioning
confidence: 66%